Evolutionary bandwidth allocation in reservation-based networks with Vickrey auctions. (9th February 2009) - Perez-Bellido, A.M.; Salcedo-Sanz, S.; Portilla-Figueras, J.; Ortiz-Garcia, E.G.; , P. Garcia-Diaz
This paper presents the description of a system for bandwidth allocation in reservation-based networks, using Vickrey auctions and an evolutionary algorithm. Our evolutionary approach performs the bandwidth allocation to agents which bid for networks resources by means of willingness-to-pay functions. It also calculates in a parallel way the price to be paid to the network's owner. We also tackle the case of the one-link model and its extension to a general and two types of special networks, ring-type and tree-type networks. Simulations performed have shown the main advantages and problems inherent to this model.